HUKUM ISLAM DALAM KERANGKA SISTEM HUKUM MASYARAKAT MODERN - Murdan, Murdan (Petita : Jurnal Kajian Ilmu Hukum dan Syariah, 2016)
The concept of Islamic law shows the principles of legal flexibility and elasticity, filling law resources in national legal system. The position of Islamic law in national legal system has been imposed by partiality of legal and political system, and also interest of modern society. In implementation step Islamic law has been required to deal with social development, including in scope of territory or period of time. Islamic law is always bringing humanity messages, cannot be assumed as the sacred norms. Islamic law is not for Allah Almighty but for kindness of human kind and universe, having the quality of secular humanists. The concept of secular humanists in Islamic law reflects in doctrine of maqashid syariah, has role as a method finding legal certainty. This method is able to fulfil the rule of law, not stated in national legal system and legal system of modern state.